Pathological mutations in PNKP trigger defects in DNA single-strand break repair but not DNA double-strand break repair - Kalasova, Ilona; Hailstone, Richard; Bublitz, Janin; Bogantes, Jovel; Hofmann, Winfried; Leal, Alejandro; Hanzlikova, Hana; Caldecott, Keith W (Nucleic acids research, 2020)
Hereditary mutations in polynucleotide kinase-phosphatase (PNKP) result in a spectrum of neurological pathologies ranging from neurodevelopmental dysfunction in microcephaly with early onset seizures (MCSZ) to neurodegeneration in ataxia oculomotor apraxia-4 (AOA4) and Charcot-Marie-Tooth disease (CMT2B2). Consistent with this, PNKP is implicated in the repair of both DNA single-strand breaks (SSBs) and DNA double-strand breaks (DSBs); lesions that can trigger neurodegeneration and neurodevelopmental dysfunction, respectively. Surprisingly, however, we did not detect a significant defect in DSB repair (DSBR) in primary fibroblasts from PNKP patients spanning the spectrum of PNKP-mutated pathologies. In contrast, the rate of SSB repair (SSBR) is markedly reduced. Moreover, we show that the restoration of SSBR in patient fibroblasts collectively requires both the DNA kinase and DNA phosphatase activities of PNKP, and the fork-head associated (FHA) domain that interacts with the SSBR protein, XRCC1. Notably, however, the two enzymatic activities of PNKP appear to affect different aspects of disease pathology, with reduced DNA phosphatase activity correlating with neurodevelopmental dysfunction and reduced DNA kinase activity correlating with neurodegeneration. In summary, these data implicate reduced rates of SSBR, not DSBR, as the source of both neurodevelopmental and neurodegenerative pathology in PNKP-mutated disease, and the extent and nature of this reduction as the primary determinant of disease severity.
Keywords: mutace; oprava DNA; Microcephaly; Seizures; Fibroblasts; mikrocefalie; fosfotransferasy s alkoholovou skupinou jako akceptorem; lidé; Apraxias; Mutation; DNA Repair; fibroblasty; enzymy opravy DNA; apraxie; DNA Breaks, Double-Stranded; DNA Repair Enzymes; Charcotova-Marieova-Toothova nemoc; dvouřetězcové zlomy DNA; Phosphotransferases (Alcohol Group Acceptor); X-ray Repair Cross Complementing Protein 1; jednořetězcové zlomy DNA; Charcot-Marie-Tooth Disease; protein XRCC1; záchvaty; DNA Breaks, Single-Stranded; Humans